Characterization of Warfarin Inhibition Kinetics Requires Stabilization of Intramembrane Vitamin K Epoxide Reductases. Issue 18 (21st August 2020) - Li, Shuang; Liu, Shixuan; Yang, Yihu; Li, Weikai
Abstract: Intramembrane enzymes are often difficult for biochemical characterization. Human vitamin K epoxide reductase (VKOR) is the target of warfarin. However, this intramembrane enzyme becomes insensitive to warfarin inhibition in vitro, preventing the characterization of inhibition kinetics for decades. Here we employ structural biology methods to identify stable VKOR and VKOR-like proteins and purify them to near homogeneity. We find that the key to maintain their warfarin sensitivity is to stabilize their native protein conformation in vitro . Reduced glutathione drastically increases the warfarin sensitivity of a VKOR-like protein from Takifugu rubripes, presumably through maintaining a disulfide-bonded conformation. Effective inhibition of human VKOR-like requires also the use of LMNG, a mild detergent developed for crystallography to increase membrane protein stability. Human VKOR needs to be preserved in ER-enriched microsomes to exhibit warfarin sensitivity, whereas human VKOR purified in LMNG is stable only with pre-bound warfarin. Under these optimal conditions, warfarin inhibits with tight-binding kinetics. Overall, our studies show that structural biology methods are ideal for stabilizing intramembrane enzymes. Optimizing toward their inhibitor-binding conformation enables the characterization of enzyme kinetics in difficult cases. Graphical abstract: Unlabelled Image Highlights: Structural biology methods enable the stabilization of intramembrane enzymes for biochemical characterization. Systematic optimization of protein stability through monitoring inhibitor efficacy allows the kinetics studies of an intramembrane thiol oxidoreductase family. Effective warfarin inhibition requires glutathione as the reductant. Warfarin stabilizes the native conformation of human vitamin K epoxide reductase.